Under ∃300 Anti-drone gun with GPS spoofing technique using COTS - Pirada Techavijit; Polkit Sukchalerm; Montawat Pitchsanupun; Natcha Kijatanath (My University, 2024)
This research presents the development of a cost-effective anti-drone gun. The system utilizes Commercial Off-The-Shelf (COTS) components for scalability and rapid development. The system employs GPS spoofing using Software-Defined Radio (SDR) devices, offering a straightforward and energyefficient solution compared to other complex anti-drone techniques. The prototype successfully manipulates coordinates, tricking commercial drones into autonomously landing in designated zones, showcasing a practical and resource-efficient approach to drone deterrence.
Keywords: UAV Applications and Optimization; IoT-based Smart Home Systems; Fire Detection and Safety Systems